2014
DOI: 10.1152/ajpheart.00177.2014
|View full text |Cite
|
Sign up to set email alerts
|

Age, aerobic fitness, and cerebral perfusion during exercise: role of carbon dioxide

Abstract: Middle cerebral artery mean velocity (MCAvmean) is attenuated with increasing age both at rest and during exercise. The aim of this study was to determine the influence of the age-dependent reduction in arterial PCO2 (PaCO2) and physical fitness herein. We administered supplemental CO2 (CO2 trial) or no additional gas (control trial) to the inspired air in a blinded and randomized manner, and assessed middle cerebral artery mean flow velocity during graded exercise in 1) 21 young [Y; age 24 Ϯ 3 yr (ϮSD)] volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 51 publications
5
42
1
Order By: Relevance
“…Flück et al. () recently demonstrated that the age‐induced decrease in cerebral perfusion is related to concomitant reductions in PaCO 2 , but that normalization of MCAv mean to that of healthy young volunteers did not affect exercise performance, which is also in agreement with the current study. Thus, the present study is the first to mechanistically address the importance of a heat‐induced reduction of MCAv mean on incremental exercise performance in the heat, and as previously reported in other settings, the diminished MCAv mean when exercising in a warm environment seems of only very limited importance for exercise performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Flück et al. () recently demonstrated that the age‐induced decrease in cerebral perfusion is related to concomitant reductions in PaCO 2 , but that normalization of MCAv mean to that of healthy young volunteers did not affect exercise performance, which is also in agreement with the current study. Thus, the present study is the first to mechanistically address the importance of a heat‐induced reduction of MCAv mean on incremental exercise performance in the heat, and as previously reported in other settings, the diminished MCAv mean when exercising in a warm environment seems of only very limited importance for exercise performance.…”
Section: Discussionsupporting
confidence: 92%
“…(b) Centrally mediated fatigue may be promoted by an insufficient O 2 delivery to the brain (Amann & Kayser, ; Rasmussen et al., ), which could become the consequence when cerebral perfusion is reduced. However, recent studies augmenting MCAv mean in hypoxic (Subudhi et al., ; Fan et al., ; Siebenmann et al., ) and normoxic (Subudhi et al., ; Flück et al., ) conditions have demonstrated that exercise capacity is not affected by changes in cerebral oxygenation, suggesting that this might also not be the case in heat‐stressed humans. Nonetheless, this remains unknown.…”
mentioning
confidence: 99%
“…; Flück et al . ). Interestingly, no significant interaction between age and exercise intensity was observed for MCA V mean by Fisher et al .…”
Section: Introductionmentioning
confidence: 97%
“…) or absolute exercise intensities (Flück et al . ) examined. These conflicting findings may relate to the smaller age difference between the groups in Fisher et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation